Development of Islamic Education Curriculum Based on Local Wisdom to Foster Students Character in Integrated Islamic High Schools - Nuryanti Siregar; Zulfani Sesmiarni; Arifmiboy; Siti Khamim; Haida Umiera Hashim (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Islamic Religious Education (PAI) in Integrated Islamic High Schools is expected to strengthen religious understanding, moral awareness, and student character. However, its implementation often remains normative, textbook-oriented, and weakly connected to students’ socio-cultural realities. This study aimed to develop and evaluate a local wisdom-based PAI curriculum device that integrates the Merdeka Curriculum, Integrated Islamic School Network (JSIT) character standards, and Angkola-Mandailing values in Padangsidimpuan City. Using a Research and Development design based on the 4D model, the study proceeded through Define, Design, Develop, and Disseminate stages. Data were collected through observation, interviews, curriculum document analysis, expert validation sheets, teacher and student practicality questionnaires, pre-test and post-test instruments, and character observation rubrics. The developed product consisted of contextualized learning objectives, learning objective sequences, teaching modules, student worksheets, and authentic assessment instruments. The findings showed that existing PAI curriculum tools had not systematically embedded local values such as Dalihan Na Tolu, Poda Na Lima, Marsialapari, hasangapon, and hamajuon. Expert validation indicated that the product was very valid, with an overall feasibility score of 91.80%. Practicality testing also showed very practical results, with teacher and student response scores of 91.00% and 86.67%, respectively. Effectiveness testing produced an N-Gain score of 0.69, indicating moderate improvement approaching the high category. Conceptually, this study positions local wisdom as a substantive curriculum foundation rather than supplementary cultural content. Practically, it provides teachers with operational tools for designing contextual, meaningful, and character-oriented PAI learning in culturally diverse Islamic school settings.